Cytogenetic considerations on the genus Astyanax (Pisces, characidae). I. Karyotypic variability - Morelli, S.; Bertollo, L. A.C.; Foresti, F. [UNESP]; Moreira F°, O.; De Almeida Toledo F°, S. (Firenze University Press, 1983)
A study was carried out on mitotic and meiotic chromosomes of four species of the genus Astyanax (Pisces, Characidae) from three different water basins in the State of São Paulo, Brazil. The following karyotypic characteristics were observed: A. bimaculatus, 2n = 50 (n = 25, FN = 86-88); A. fasciatus, 2n = 46 (n = 23, FN = 90); « A. fasciatus » from the Juquiá river, 2n = 48 (n = 24, FN = 94); A. schubarti, 2n = 36 (n = 18, FN = 70) and A. scabripinnis paranae, 2n = 50 (n = 25, FN = 90-92). The diversity in the number and morphology of the chromosomes suggests a model of non-conservative karyotypic evolution in this genus, with chromosome rearrangements of the centric fusion/fission type and/or inversion playing an important role in these alterations. On the basis of its characteristics, A. schubarti has the most differentiated karyotype and, in view of the low diploid number and small number of subtelocentric-acrocentric chromosomes, is probably of most recent origin. The two karyotypes encountered in A. fasciatus raise the possibility that « A. fasciatus » from the Juquia river may represent a new subspecies, or even a new species, of fasciatus. The absence of karyotype differences between males and females, means that all four species lack differentiated sex chromosomes. © 1983 Taylor & Francis Group, LLC.